A SOLUTION EXPANDING GENERAL INFORMATION NKVS-27 FOR AIR OPERATION IN THE HEAD OFFICE - Ngọc (Journal of Military Science and Technology, 2021)
The paper presents the structure and information exchange mechanism between the components of the NKVS-27 Ground-to-Air Complex. Focus on data exchange structure, research, construction and implementation of the two-way information expansion plan from NKVS-27 surface-to-air complex working with Su-30MK2 aircraft for command and control flight at Headquarters. The results achieved when on-site testing.